Features of circuit-topological design and layout simulation of the operational amplifier on CMOS structures for biomedical applications - Kogut, I.T.; Dzundza, B.S.; Holota, V.I.; Hryha, V.M.; Shtun, M.V.; Morgun, A.V.; Pivnenko, V.M. (Physics and Chemistry of Solid State, 2024)
The paper presents the results of circuit topological design and layout simulation of the operational amplifier based on complementary (CMOS) structures using the standard industrial planar CMOS technology on KDB-40 silicon wafers with n-type conductivity wells. The operational amplifier was developed for the implementation of an integral converter signals (ICS) of photoplethysmography, the feature of which is the amplitude regulation and filtering of the constant component in the amplified signal from the diode photosensitive element in the wave range of 400 ÷ 1040 nm. The developed ICS is suitable for creating real devices in an integrated implementation, as an element of sensor microsystems-on-a-crystal or smart sensors.